Evaluation of Flood Control in Pakal District With The Construction of The Sumber Rejo Flood Pump in Surabaya City - Bob Sandy Rahardjo; Adi Prawito; Ronny Durrotun Nasihien Nasihien (NAROTAMA UNIVERSITY, Indonesia, 2021)
Flood has always been expected in the rainy season at the Pakal District before 2019, where rainwater flows from Benowo channel to the Sumber Rejo channel and backwater flows from Lamong river to the Sumber Rejo channel. These water “attacks” from the two sides of the water bodies made Sumber Rejo flood every rainy season. In this analysis the maximum water flow rate in Sumber Rejo channel within the 20-year period (Q20) is 22,57 m3/second. To eleminate flood in Sumber Rejo channel, a flood pump station is needed to pump the waterflow from Benowo channel dan stop the backwater infiltrating from the Lamong river. Two flood pumps with a total flow rate of 6 m3/second are already installed and running at the moment, while the optimal capacity of this flood pump station should be 12 m3/second. A large water storage with capacity around 88.712 m3 is already built to keep the water elevation low enough to not overflow the Sumber Rejo channel.